PERANAN BUM DESA DALAM MENINGKATKAN KESEJAHTERAAN DESA - Mai Simahatie; Munawarah, Munawarah; Cut Santika; Fatimah Zuhra; Rahmi, Rahmi; Zahara, Zahara (Sean Institute, 2022)
The Role of Village Owned Enterprises (Bumdes) in Improving Community Welfare in Kuala Raja Village, Bireuen Regency. Development is an orientation in activities to advance the nation, including processes, one of which is village development which must be carried out in a planned manner and touch the real needs of rural communities. regarding the role of Village Owned Enterprises (BUMDes) In improving the welfare of the community so that the BUMDes program is effective and targeted, how is the role of village-owned enterprises (BUMDes) in improving the welfare of the people in the village. Kuala Raja village. This PKM aims to find out how the role of BUMDes in improving the welfare of the community. The results of this pkm show that: 1) Seeing from the activities of BUMDes, it is clear that it helps the people of Kuala Raja to further improve their welfare because seen from the programs that are being run, there is nothing that harms the community but adds or increases he income of the community and the income of the Kuala Raja village.